Pemberdayaan Masyarakat Peduli Makanan Sehat Melalui Deteksi Berbasis IPTEK Menggunakan Senyawa Bahan Alam pada Bahan Tambahan Pangan Berbahaya - Yuni Fatisa; Lisa Utami (MENARA RIAU, 2020)
Along with the increasing need for non-perishable foodstuffs, hazardous chemical food additives (FA) such as borax and formalin are widely used in the food industry, such as in making wet noodles, meatballs, rice cake, tofu, and others. This dangerous chemical FA is usually used as a food preservative, even though these chemicals are poisonous and dangerous to human health so that their use is strictly prohibited by the government. In order to anticipate the wider negative impact of the use of hazardous chemical FA added to foodstuffs, it is necessary to carry out counseling and socialization activities regarding healthy food free of hazardous chemical FA by mastering the technology for identifying food additives and handling them. This activity uses a method of mentoring the community learning process in the form of counseling and training. The target of the socialization activity was the majelis taklim of Babussalam Mosque, Tampan District, Pekanbaru City. The overall implementation of the activity exceeded the desired target because 96% of the participants understood food additives, 83.3% understood tips on recovering healthy and hazardous FA-free food, and 84% were interested in making hazardous chemical FA detection tools.